(untitled) (Mustansiria Dental Journal, 2018)
Background: Squamous cell carcinoma of the oral cavity constituted a major health problem and can be a leading cause of death. Several studies link high risk Human papillomavirus -16 to oral squamous cell carcinoma as an important etiological factor. Several molecular markers have also been the subject of an intense research work, trying to clarify their role in oral carcinogenesis. Of these, the cancer suppresser gene P53 has been extensively studied. Aim of the study: to detect the association of the molecular markers Human papillomavirus -16, in the oral Squamous cell carcinoma using in situ hybridization technique and To correlate Human papillomavirus -16 with clinical data (age, sex, risk factors grade &stage). Material & Methods: Tumor tissues from 33 patients with newly diagnosed as oral squamous cell carcinoma & who were surgically treated collected, formalin fixed & paraffin embedded. Sections on charged slides were made from each tissue block and submitted to in situ hybridization technique utilizing Human papillomavirus -16, cDNA probe. Results: Human papillomavirus -16 was localized by in situ hybridization specifically within the nuclei of cancer cell it was detected in (27) (81.8%) of 33 oral squamous cell carcinoma patients. Most of Human papillomavirus -16 positive patients were within the age group (50-59) years. However, there was no significant correlation between Human papillomavirus -16 positive &age. No significant correlation was found to sex &risk factors (smoking &alcohol consumption) either. Most of cases were moderately differentiated squamous cell carcinoma (79%). however no significant correlation was detected regarding histopathological grading or clinical staging with Human papillomavirus -16. Conclusions: Oral HPV-16 infections are strongly associated with OSCC. Among subject with or without the established risk factor of tobacco& alcohol use